From Freshers to Trailblazers: The Campus Chronicles of Vini, Sam, Dev, and Lolita - Vinisha R (ILN Journal: Indian Literary Narratives, 2025)
This article examines Vini, Sam, Dev, and Lolita's four years at VIT Vellore, showing how they changed from unconfident freshmen to cherished campus heroes. This study uses qualitative research techniques, such as structured interviews and reflective journaling, to document the dynamic interactions between friendship, resilience, leadership, and mentoring. Their story exemplifies the critical role of community involvement, leadership training, and peer support in promoting academic and personal development. Their narrative stresses the development of a culture of respect, support, and empowerment in addition to individual success. Their development emphasizes how important social belonging, psychological fortitude, and proactive leadership are to education more broadly in modern higher education environments. This article clarifies how college friendships can significantly impact leadership trajectories, emotional intelligence, and identity development, which benefits both the individuals and their communities.